REKONSTRUKSI PENDIDIKAN ISLAM KONTEMPORER (SEBUAH TINJAUAN FILSAFAT PENDIDIKAN ISLAM) - Usiono Usiono (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Islamic education efforts to transform by adapting to technological developments without applying Islamic teachings. Islamic education encourages to change and maximize potential in carrying out the obligations of a leader with full sense. A person who is tough and loves knowledge from outside of Islamic education, the social community will experience changes for the better based on the needs and needs of the times. The paradigm of Islamic education tends to be more oriented towards the humanities and social sciences, whereas science and technology development is absolutely necessary. Facing the era of globalization, the actualization of contemporary Islamic education must also have clear directions and objectives, for example carrying out an educational revolution in Indonesia; 1) Science education, 2) Creativity education, 3) Digital education, 4) Higher education. In addition to being able to create concepts with basic values and strategies that are productive and anticipatory, facing future developments in the future, they must also be able to maintain basic values that are truly believed to be maintained and developed, including entering and even adapting to the development of technology through its use and utilization as a source and learning media.